Expansion of the object of surveillance for occupational accidents: history and challenges underwent by a reference center aiming at prevention - Gouveia Vilela, Rodolfo Andrade de; Jackson Filho, Jose Marcal; Pereira Querol, Marco Antonio; Bezerra Gemma, Sandra Francisca; Conti Takahashi, Mara Alice; Pereira Gomes, Marcos Hister; Canale Duracenko, Sandra Renata; Almeida, Ildeberto Muniz de [UNESP] (Abrasco, 2018)
The Surveillance System for Occupational Accidents (Sistema de Vigilancia em Acidentes de Trabalho - SWAT) established by Reference Center for Workers' Health (Centro de Referencia em Satide do Trabalhador - CEREST-Piracicaba) in 2003 represents an experience consolidated according to the guidelines formulated by the National Network for Integral Care of the Workers' Health (Rede Nacional de Atencao Integral a Saude do Trabalhador - RENAST). The present article analyzes the history and development of SWAT at CEREST - Piracicaba from the perspective of cultural-historical activity theory. The historical data comprise interviews, documents and observations performed by the researchers. Analysis showed that the studied activity underwent two cycles of expansion. During the first cycle, CEREST actions sought to adequate the targeted companies to the legislation in vigor. During the second cycle, actions aimed at introducing changes relative to organizational determinants in the targeted companies that CEREST staff identified as causes of accidents. A new modality of formative intervention, called Change Laboratory (CL), seems to be useful to attain the goal of prevention; it involves analysis of the causes of accidents, activity remodeling and implantation of solutions by developing agency in the targeted organizations.
Keywords: Workers' health surveillance; Occupational health services; Working conditions; Expansive learning theory